Exposição humana ao metilmercúrio em comunidades ribeirinhas da Região do Tapajós, Pará, Brasil - PINHEIRO, Maria da Conceição Nascimento (2011)
Evaluation of total human exposure to mercury and methylmercury was effected in riverine villages along the Tapajos river and in the metropolitan area of Belem city, state of Para, Brazil, by using total mercury and methylmercury concentrations in hair samples in 1994 and 1995. It was observed that average concentrations of total mercury are in a range from 2 ± 1µg/g-1 to 20.5 ± 12.1µg/g-1. While methylmercury average concentration varies from 1.4 ± 0.7µg/g-1 to 18.5 ± 11µg/g-1. These results confirm mercury contamination in the Tapajos river and possible appearance of mercury intoxication symptoms, and recommends the monitoring of compounds in hair samples as well as the need for epidemiological and clinical studies for human health prevention and control of mercury intoxication.